Prevalence and risk factors for seclusion and restraint in old-age psychiatry inpatient units - Chieze, Marie (BMC Psychiatry, 2021)
BACKGROUND AND OBJECTIVES: Coercion in psychiatry is legally tolerated as a last resort. The reduction of the use of coercion is a shared goal of hospital administrators, medical and nursing staff and representatives of patients and families but requires the identification of risk factors for coercion. These risk factors in geriatric psychiatric inpatient settings are not well known, especially regarding seclusion. Through examining the prevalence of coercion and patients’ characteristics, this study aims to identify risk factors for coercion in elderly people. METHODS: The use of coercion in the geriatric psychiatry division of Geneva University Hospital in 2017 was retrospectively analyzed. The incidence rate ratios were estimated with multivariable Poisson regressions to assess risk factors for coercion. RESULTS: Eighty-one of 494 patients (16.4%) experienced at least one coercive measure during their stay (mainly seclusion). The risk factors for coercion were younger age, male gender, being divorced or married, cognitive disorders, high item 1 of the Health of the Nation Outcome Scales (HoNOS) score (overactive, aggressive, disruptive or agitated behavior) at admission, previous psychiatric hospitalizations and involuntary referrals from the emergency department. Other disorders and global HoNOS scores were not associated with the use of coercion. CONCLUSION: Higher risks of coercion were outlined in men with cognitive disorders, agitated behaviors, and previous psychiatric hospitalizations. They differed from those observed in younger adults in terms of age, civil status, disorders, global HoNOS scores and referrals. Therefore, geriatric psychiatric populations should be specifically investigated for the development of interventions aiming coercion reduction.